Mixed convection in an Horizontal Rectangular Duct Including interior Circular Core with Time periodic Boundary Condition - H. Al-Hafidh, Manal (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
Numerical Investigation was done for steady state laminar mixed convection and thermally and hydrodynamic fully developed flow through horizontal rectangular duct including circular core with two cases of time periodic boundary condition, first case  on the rectangular wall while keeping core wall constant and other on both the rectangular duct and core walls. The used governing equations are continuity momentum and energy equations. These equations are normalized and solved using the Vorticity-Stream function and the Body Fitted Coordinates (B.F.C.) methods. The Finite Difference approach with the Line Successive Over Relaxation (LSOR) method is used to obtain all the computational results the (B.F.C.) method is used to generate the grid of the problem. A computer program (Fortan 90) is built to calculate Nusselt Number (Nu) in steady state. The fluid Prandtl number is 0.7 Rayleigh Number  1